Preserving privacy of online digital physiological signals using blind and reversible steganography. (November 2017) - Shiu, Hung-Jr; Lin, Bor-Sing; Huang, Chien-Hung; Chiang, Pei-Ying; Lei, Chin-Laung
Highlights: Privacy preserving is important to keep private data of patients. The proposed research adopts steganography using modified error correcting coding to achieve privacy preserving. The capacity performance is higher than previous works. The time complexity and robustness are evaluated. Abstract: Background and objective: Physiological signals such as electrocardiograms (ECG) and electromyograms (EMG) are widely used to diagnose diseases. Presently, the Internet offers numerous cloud storage services which enable digital physiological signals to be uploaded for convenient access and use. Numerous online databases of medical signals have been built. The data in them must be processed in a manner that preserves patients' confidentiality. Methods: A reversible error-correcting-coding strategy will be adopted to transform digital physiological signals into a new bit-stream that uses a matrix in which is embedded the Hamming code to pass secret messages or private information. The shared keys are the matrix and the version of the Hamming code. Results: An online open database, the MIT-BIH arrhythmia database, was used to test the proposed algorithms. The time-complexity, capacity and robustness are evaluated. Comparisons of several evaluations subject to related work are also proposed. Conclusions: This work proposes a reversible, low-payload steganographic scheme for preserving the privacy of physiological signals. An ( n,   m )-hamming code is used to insert ( n  −  m ) secret bits into n bits of a cover signal. The number of embedded bits per modification is higher than in comparable methods, and the computational power is efficient and the scheme is secure. Unlike other Hamming-code based schemes, the proposed scheme is both reversible and blind.